(untitled) (Asian Journal of Social Science Studies, 2022)
As a theoretical concept, the introduction of local mobile culture is very helpful to the study of Changsha-Zhuzhou-Xiangtan public transport. In this paper, GIS public transport policy is used as the carrier of Changsha-Zhuzhou-Xiangtan mobile culture to explore the regional differences of local mobile cultures. The measure of local mobility culture proposed in this paper is composed of the difference of road distance between regions and the efficiency of mobility, which reflects the influence of these two potential factors. In addition, the results also support the prediction of Changsha-Zhuzhou-Xiangtan public transport, and the latitude of local mobile culture has a substantial relationship with transportation distance and tool use.